Novel Analysis of Fractional-Order Fifth-Order Korteweg–de Vries Equations. (23rd May 2022) - Khoshaim, Ahmed B.; Naeem, Muhammad; Akgul, Ali; Ghanmi, Nejib; Zaland, Shamsullah
Abstract : In this paper, the ρ -homotopy perturbation transformation method was applied to analysis of fifth-order nonlinear fractional Korteweg–de Vries (KdV) equations. This technique is the mixture form of the ρ -Laplace transformation with the homotopy perturbation method. The purpose of this study is to demonstrate the validity and efficiency of this method. Furthermore, it is demonstrated that the fractional and integer-order solutions close in on the exact result. The suggested technique was effectively utilized and was accurate and simple to use for a number of related engineering and science models.